Konsultasi Publik Pengembangan Taman Botani Sebagai Ruang Terbuka Hijau Secara Daring di Kutai Timur - Titis Hutama Syah; Ery Mulyadi; Mufti Perwira Putra; Dhani Aryanto; Arbain Arbain (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has resulted in several government-related activities being carried out online. One of them was a public consultation on the development of the Taman Botani Kutai Timur. This activity aimed to find out the recent conditions and potential developments that can be reached from Taman Botani as a green open area. The activity was carried out through focus group discussions, presenting researchers and practitioners from parties representing the central government, provincial governments, district governments, relevant government institutions, academics, community institutions, and other interested communities. The meetings held revealed that Taman Botani has potential to be developed for the better. One of the suggestions that emerged was to develop it into a regional botanical garden. Otherwise, its successful development requires a strong commitment from the local government regarding policy formulation and funding allocation. In addition, the development of Taman Botani requires monitoring from the community in the form of policy advocacy.